Salem on the Thames: Moral Panic, Anti-Zionism, and the Triumph of Hate Speech at Connecticut College - Landes, Richard Allen (Antisemitism in America, 2020)
Frontmatter -- Contents -- Preface -- Introduction -- Andrew Pessin’s Facebook Post during Operation Protective Edge -- Condensed Timeline -- 1. The Post: On Truth and Metaphor -- 2. The Shameful Dishonesty of It All: An Annotated Chronology from the Perspective of the Victim -- 3. The People: McCarthyism, New London Style -- 4. Connecticut College Acts Out a Staged Emergency -- 5. “I Was Rude, You Were Evil”: Reflections on Academia, Liberalism, and the Betrayal of Andrew Pessin -- 6. The Pessin Case: The Response of Jewish Colleagues -- 7. What Connecticut College’s Andrew Pessin Affair Teaches Us -- 8. Reflections on Academia and Freedom: The Case of Connecticut College, Spring 2015 -- 9. Pessin, Ironic Prophet: The Liberal Emperor’s New Clothes of Humanitarian Racism -- Bibliography